The Effects of Diode Laser (980 nm Wavelength) and Chlorhexidin Gel in the Treatment of Chronic Periodontitis - Birang, Reza; Yaghini, Jaber; Adibrad, Mahdi; Kiany, Sima; Mohammadi, Zinab; Birang, Ehsan (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: The aim of the present study was to investigate the effects of SRP assisted by the two clinical treatment methods of diode laser or Chlorhexidine Gel applications in comparison with SRP alone. METHODS: Eight patients with moderate to severe chronic periodontitis, each with at least three pockets 4–7 mm deep, were selected for this study. Over 66 pockets were selected and randomly treated by either scaling and root planning (SRP) alone, or by SRP + diode laser (1.5 W,980 nm,30sec, continuous wave)(laser group),or by SRP + chlorhexidine gel-xanthan based (gel group). The clinical indices (probing pocket depth [PPD], clinical attachment level [CAL], and papillary bleeding index [PBI] mean score) and microbiological index (total bacterial count [TBC]) before, 1 month and three months after treatment were measured and evaluated. RESULTS: The results showed that SRP assisted by chlorhexidine gel and diode laser therapies exhibits better results than SRP alone in reducing PPD, improving clinical CAL, and reducing PBI mean score and TBC (p < 0.05) both at one month and three months follow ups. Comparison of clinical indices between the laser group and the gel group showed no significant differences at neither of the follow up stages, but in 3 months follow up interval, the TBC reduction in the laser group was significantly more than the gel group (P < 0.05). CONCLUSION: Treatment with diode laser or chlorhexidine gel as an adjunct to SRP may improve periodontal and microbiological indices compared to SRP alone. Diode laser showed better bactericidal effects in long term.